Preparation and In-Vitro, Ex-Vivo Evaluation of Oral Dosage Form Containing Mirtazapine Nano suspension - Hiba Ezzat Hamed (Journal of Global Pharma Technology, 2016)
The aim of this study is to formulate and evaluate mirtazapine nanoparticles using solvent anti solvent technology. Mirtazapine is practically insoluble in water which acts as antidepressant. Itis prepared as nano particles in order to improve its solubility and dissolution rate. Mirtazapine nanoparticles were prepared using anti-solvent precipitation method using different stabilizers (poloxamer 188, poloxamer 407, TPGS and SLS) at drug: stabilizer ratio 1:1 and 1:2, alone and in combination. Mirtazapine nanoparticles were characterized by particle size analysis, percentage of drug entrapment efficiency, in vitro dissolution study, ex vivo study, Fourier transform infrared spectroscopy, differential scanning calorimetry and atomic force microscope. Freeze dried nanoparticles were compressed into tablets by direct compression method using different excipients which are microcrystalline cellulose PH 102, starch, and Mg stearate as diluent, binder, and lubricant; The results showed that the particle sizes were ranged from 272 to 691 nm at drug: stabilizer ratio 1:1 and from 146 to 572 nm at drug : stabilizer ratio 1:2. Stabilizers combination has good surface affinity and could form a substantial mechanical and thermodynamic barrier at the interface of dug molecule. As the concentration of stabilizer increases the particle size decreases at fixed drug concentration. % EE was ranged from 75.5% to 95.9%. On the other hand dissolution rate increasing as the particle surface area is increase due to reduction of particle size to the nano range.Keywords: Mirtazapine, Nanoparticles, Particle Size, Poloxamer.